New Role Management Nasopharyngeal Carcinoma Patient in General Hospital Haji Adam Malik Medan during COVID-19 Pandemic - Sholahuddin Adlan Simatupang; Farhat Farhat; Elvita Rahmi Daulay (TALENTA PUBLISHER, 2021)
Introduction: Nasopharyngeal carcinoma (NPC) is a type of squamous cell carcinoma that develops from the nasopharyngeal epithelial cells and has become one among the most popular frequent malignancy in the head and neck. When patients with cancer are diagnosed with COVID-19, more intense surveillance or treatment should be considered. Discussion: In the COVID 19 pandemic, Personal protection provisions should be strengthened. created for cancer patients and cancer survivors. To avoid the spread of COVID-19, many improvements have been made in the treatment of NPC patients at the Haji Adam Malik General Hospital in Medan. Conclusion: The management carried out on NPC patients, there are several examinations that the patient needs to do first in the COVID 19 pandemic at the General Hospital Haji Adam Malik Medan